PENGARUH KOMPONEN ARUS KAS DAN LABA AKUNTANSI TERHADAP RETURN SAHAM DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERATING: Studi Empiris pada Perusahaan Sektor Industri yang Terdaftar di Bursa Efek Indonesia - Nur Azizah; Desy Purwasih (LPPM Universitas Bina Bangsa, 2023)
This study aims to examine the effect of operating cash flow, investment cash flow, funding cash flow and accounting profit on stock returns with company size as a moderating variable. Using the purposive sampling method, the research sample was 14 companies with 5 years of research or equivalent to 70 data. The results showed that simultaneously operating cash flow, investment cash flow, funding cash flow and accounting profit together affect stock returns. Partially, only operating cash flow has no effect on stock returns, while investment cash flow, funding cash flow and accounting profit affect stock returns. In moderation, the size of the company is unable to moderate the relationship between operating cash flow, investment cash flow, funding cash flow and accounting profit to stock returns